Do We Need Exercise Tests to Detect Gas Exchange Impairment in Fibrotic Idiopathic Interstitial Pneumonias?. (29th July 2012) - Wallaert, Benoit; Wemeau-Stervinou, Lidwine; Salleron, Julia; Tillie-Leblond, Isabelle; Perez, Thierry
Abstract : In patients with fibrotic idiopathic interstitial pneumonia (f-IIP), the diffusing capacity for carbon monoxide (DLCO) has been used to predict abnormal gas exchange in the lung. However, abnormal values for arterial blood gases during exercise are likely to be the most sensitive manifestations of lung disease. The aim of this study was to compare DLCO, resting PaO2, P(A-a)O2 at cardiopulmonary exercise testing peak, and oxygen desaturation during a 6-min walk test (6MWT). Results were obtained in 121 patients with idiopathic pulmonary fibrosis (IPF, n = 88 ) and fibrotic nonspecific interstitial pneumonias (NSIP, n = 33 ). All but 3 patients (97.5%) had low DLCO values (<LLN) whereas only 66.6% had low KCO; 42 patients (65%) exhibited resting hypoxemia (<75 mmHg); 112 patients (92.5%) exhibited a high P[(A-a)O2 ], peak (>35 mmHg) and 100 (83%) demonstrated significant oxygen desaturation during 6MWT (>4%). Interestingly 27 patients had low DLCO and normal P(A-a)O2, peak and/or no desaturation during the 6MWT. The 3 patients with normal DLCO also had normal PaO2, normal P(A-a)O2, peak, and normal oxygen saturation during 6MWT. Our results demonstrate that in fibrotic IIP, DLCO better defines impairment of pulmonary gas exchange than resting PaO2, exercise P(A-a)O2, peak, or 6MWT SpO2 .